Identifying non-essential uses to phase out substances of very high concern under REACH - Borchert, Flora; Figuière, Romain; Cousins, Ian T.; Rudén, Christina; Ågerstrand, Marlene (Frontiers in Toxicology, 2024)
The essential use concept aims to better protect consumers, vulnerable groups, and the environment from the most harmful chemicals by phasing out uses considered non-essential for society. Given the lack of empirical research evaluating this novel approach for chemical management in real-world settings, the aims of the present analysis were to 1) investigate if the information provided in applications for authorisation under REACH allowed for the identification of non-essential uses of substances of very high concern (SVHCs), and 2) identify data gaps, challenges and potential needs for revising the assessment criteria to effectively implement the essential use concept in the REACH authorisation. In total, 100 uses covering 11 SVHCs were analysed. 4-(1,1,3,3-tetramethylbutyl) phenol (OPnEO) and chromium trioxide were among the most frequently used substances, covering 42% and 35% of the analysed uses. Using the current essential use criteria, 55% of all analysed uses were categorised as essential, while 10% were categorised as non-essential. Potentially, authorisations would not have been granted for the identified non-essential uses under REACH if the concept had been implemented at the time. However, for 35% of the uses it was not possible to assess their essentiality and these uses were therefore categorised as “complex.” These challenges were due to the multiple purposes of the technical function, lack of detailed information on the spectrum of end-uses, and difficulties in interpreting the essential use criteria. Consequently, for a successful implementation of the essential use concept, we recommend the European Commission to develop guidance for applicants and refine the essential use criteria to ensure a transparent and resource-efficient authorisation procedure under REACH.